The Turn to the Archipelagic-Oceanic in Recent Critical Island Studies in Southeast Asia - Campomanes, Oscar V. (Archīum Ateneo, 2024)
This introductory essay briefly maps Critical Island Studies as it is so dubbed in Southeast (nesology/nissology, elsewhere) to be able to mark how the six contributions to this Forum Kritika reflect some of the most characteristic aspects and the latest conceptual turns of critical writing and scholarship in the field. A turn to the archipelagic-oceanic as the object of theorizing and critical study is observed to be the recent trend, itself reflected in the various essays here, with their choices of topics and texts in Indonesian, Taiwanese, Korean, and Filipino conjunctures and contexts.